Enhanced anode performance of micro/meso-porous reduced graphene oxide prepared from carbide-derived carbon for energy storage devices. (September 2015) - Yeon, Sun-Hwa; Yoon, Hana; Lee, Sang-Ho; Kim, Ji Eun; Lim, Sungnam; Shin, Kyoung-Hee; Park, Ho Seok; Jin, Chang-Su; Ahn, Wook; Cheong, Hae-Won; Choi, Yusong; Yu, Hye-Ryeon
Abstract: Micro/meso-porous reduced graphite oxide (MMRGO) nanosheets were produced using precursor carbide-derived carbon (CDC), which was produced at a high temperature of 1200 °C, through a massive wet chemistry synthetic route involving graphite oxidation and microwave reduction. X-ray diffraction (XRD) and transmission electron microscopy (TEM) show that the MMRGO nanosheets were fabricated with 2–3 layers and ripple-like corrugations. N2 sorption isotherms confirmed that micro/meso-pores coexisted in the RGO sample from CDC. In the anode application of Li-ion batteries, this RGO sample had an enhanced capacity performance at the 0.1 C rate and 1 C rate, with ∼1200 mAh g −1 at the 100th cycle and ∼1000 mAh g −1 at the 200th cycle, respectively.